Curating the Nation: The Politics of Recognition in a Bahamian National Museum - Lee, Maria A. (International Journal of Bahamian Studies, 2015)
The Commonwealth of The Bahamas achieved independence in 1973, yet plans to open a national museum have not reached fruition. Drawing on this vacancy, I analyze what could be entailed in thinking about the Bahamian nation from the curatorial standpoint of a national museum. I employ a framework grounded in museum anthropology to identify specific areas that this institution might consider. In particular, I argue for engagement with the politics of recognition of multiple perspectives and heritages within the Bahamian community. While many kinds of diverse experiences can be explored, I address the opportunity to rethink race, color, and Bahamian national identity in light of an exclusionary black Bahamian rhetoric deployed in early nation-building projects from 1973 to 1992. I also explore previous African-centered curatorial frameworks in various Caribbean national museum systems to caution against this one-dimensional regional trend. More broadly, I consider how a national museum of this nature could facilitate a more fluid notion of Bahamian national identity.